2018
DOI: 10.1039/c8dt01276h
|View full text |Cite
|
Sign up to set email alerts
|

Solvent effects on the crystal structure of silver pentacyanocyclopentadienide: supramolecular isomerism and solvent coordination

Abstract: Several coordination polymers of silver(i)-pentacyanocyclopentadienide (PCC) were studied by X-ray diffraction to examine the effects of different solvents on supramolecular isomerism of the PCC-ligand. While alcohols yield supramolecular isomers of [Ag(PCC)] without coordination of solvent molecules, less polar solvents show coordinate binding. The influence of solvent polarity can be observed by a gradual change in the lattice structure featuring distinct motifs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…[3,17] And, indeed, the occurrence of weak Ag-cyclopentadienyl ring interactions was also found in the structures of Ag[C 5 (CN) 5 ], with Ag-centroid distances of 3.36 and 3.69 Å. [21] Considering the much smaller ionic radius of Ag + (1.15 Å for CN 6), [18] the interactions in the Tl compound appear much stronger.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…[3,17] And, indeed, the occurrence of weak Ag-cyclopentadienyl ring interactions was also found in the structures of Ag[C 5 (CN) 5 ], with Ag-centroid distances of 3.36 and 3.69 Å. [21] Considering the much smaller ionic radius of Ag + (1.15 Å for CN 6), [18] the interactions in the Tl compound appear much stronger.…”
Section: Resultsmentioning
confidence: 76%
“…It has also been pointed out at several occasions, that there exist close structural similarities between Tl + and Ag + (and sometimes K + ) compounds [3,17] . And, indeed, the occurrence of weak Ag‐cyclopentadienyl ring interactions was also found in the structures of Ag[C 5 (CN) 5 ], with Ag‐centroid distances of 3.36 and 3.69 Å [21] . Considering the much smaller ionic radius of Ag + (1.15 Å for CN 6), [18] the interactions in the Tl compound appear much stronger.…”
Section: Resultsmentioning
confidence: 81%
“…These changes are mainly due to the decrease in the charge density of the pyridine ring when the pyridyl N 1 atom of TPPA coordinated with Ag + /I + . 62,63 The coordination with Ag/I + to form MOF/XOF-TPPA causes signicant perturbations in the magnetic environments of TPPA (Fig. 1c).…”
Section: Resultsmentioning
confidence: 99%
“…These changes are mainly due to the decrease in the charge density of the pyridine ring when the pyridyl N 1 atom of TPPA coordinated with Ag + /I + . 62,63…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of a crystal structure determination, these authors postulated a 'polymeric structure in which the iron is in an approximately octahedral environment', in which 'each PP group bridges three iron atoms'. Within the last 15 years, the coordination chemistry of the pentacyanocyclopentadienide anion has been studied intensively by us and others (Su ¨nkel & Reimann, 2013;Nimax et al, 2018;Blockhaus & Su ¨nkel, 2021;Bacsa et al, 2011;Less et al, 2013). These studies showed that [C 5 (CN) 5 ] À could behave either as a noncoordinating anion or use one to its five cyano groups for coordination, sometimes even in a bridging 2 -1 : 1 fashion.…”
Section: Introductionmentioning
confidence: 99%